Effect of Perioperative Blood Transfusion on the Postoperative Prognosis of Ruptured Hepatocellular Carcinoma Patients With Different BCLC Stages: A Propensity Score Matching Analysis - Xia, Feng; Zhang, Qiao; Huang, Zhiyuan; Ndhlovu, Elijah; Zhang, Mingyu; Chen, Xiaoping; Zhang, Bixiang; Zhu, Peng (Frontiers in Surgery, 2022)
Abstract Background and aim： The effect of perioperative blood transfusion on the prognosis of ruptured hepatocellular carcinoma (rHCC) patients with different Barcelona Clinic Liver Cancer (BCLC) stages is not clear. We identified the independent predictors of perioperative blood transfusion (PBT)for postoperative rHCC and investigated the effects of perioperative blood transfusion on the prognosis of rHCC patients at different BCLC stages. Methods A total of 340 patients who underwent curative hepatectomy for rHCC between January 2010 and March 2018 were abstracted from the databases of two centers. 166 patients underwent PBT. The prognosis of patients who received PBT and those who did not receive PBT was compared before and after propensity score matching (PSM) in different BCLC stages. Univariate and multivariate Cox regression analyses were also used to identify independent predictors of PBT. Results We divided the 340 patients into two groups: early tumor stage (BCLC-A) n = 196 and advanced tumor stage (BCLC-B/C) n = 144. Overall, the median survival time of the PBT group was lower than that of the non-PBT group before and after PSM. However, in the BCLC-BC group, the prognosis of patients with PBT was not statistically different from that of patients without blood transfusion. Univariate Cox analysis showed that PBT was a risk factor affecting the overall survival (OS) and recurrence-free survival (RFS) in BCLC-A, and PBT was not a risk factor for poor OS and RFS in BCLC-B/C. Conclusion PBT has a negative impact on the postoperative prognosis of patients with rHCC in the early stage but has no significant impact on the postoperative prognosis of patients with rHCC in the advanced stage.